2012
DOI: 10.1155/2012/709483
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Properties of Longan (Dimocarpus longanLour.) Pericarp

Abstract: This study examined the antioxidant and anti-inflammatory activities of the water extract of longan pericarp (WLP). The results showed that WLP exhibited radical scavenging, reducing activity and liposome protection activity. In addition, WLP also inhibited lipopolysaccharide (LPS)-induced nitric oxide (NO) production in macrophages. Further, administration of WLP, in the range of 100–400 mg/kg, showed a concentration-dependent inhibition on paw edema development following carrageenan (Carr) treatment in mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 29 publications
2
25
1
1
Order By: Relevance
“…Previous study has shown the anti-inflammatory effect of longan flower, twigs, and pericarp (Ho et al, 2007;Huang et al, 2012;Wang et al, 2012). On the other hand, fresh and dried longan aril extracts significantly increased basal prostaglandin E 2 (PGE 2 ) production and tended to elevate LPSstimulated PGE 2 production in RAW264.7 macrophages (Huang and Wu, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Previous study has shown the anti-inflammatory effect of longan flower, twigs, and pericarp (Ho et al, 2007;Huang et al, 2012;Wang et al, 2012). On the other hand, fresh and dried longan aril extracts significantly increased basal prostaglandin E 2 (PGE 2 ) production and tended to elevate LPSstimulated PGE 2 production in RAW264.7 macrophages (Huang and Wu, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Inflammatory pain is primarily due to the sensitization of specific classes of nociceptive neurons by the direct action of inflammatory mediators [1]. Extensive studies have demonstrated that various pro-inflammatory mediators, including tumor necrosis factor alpha (TNF-α), interleukin-6 (IL-6), and nitric oxide (NO), play an important role in inflammatory pain [2][3][4]. Additionally, cyclooxygenase-2 (COX-2) contributes to the production of prostaglandin E 2 (PGE 2 ) [5], which is a major mediator of inflammatory pain.…”
Section: Introductionmentioning
confidence: 99%
“…Longan is found widely in southeast Asia, including China, Thailand, Vietnam, and other countries (Rangkadilok, Worasuttayangkurn, Bennett, & Satayavivad, 2005). The fresh pulp of longan is juicy and sweet, with various nutritional components, and considered to have health benefits in Traditional Chinese Medicine (TCM) (Huang et al, 2012). Although flesh is widely used, the pericarp of longan is usually discarded as a by-product of the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…Previous phytochemical studies have suggested that an abundance of phenolics such as (-)-epicatechin, gallic acid derivatives (Sun, Shi, Jiang, Xue, & Wei, 2007) and ellagic acid derivatives (Rangkadilok et al, 2005) exist in longan peel. Longan pericarp extracts or its constituents displayed anti-inflammatory (Huang et al, 2012), antioxidant (Jiang et al, 2009;Sun et al, 2007) and antityrosinase activity (Prasad et al, 2010) which may be beneficial to certain human chronic disease treatment according to published report. However, little information has been reported with regard to the anti-diabetic effects of longan pericarp to date.…”
Section: Introductionmentioning
confidence: 99%